Geochemical and Reservoir Characteristics of the Upper Triassic Continental Shale in the Sichuan Basin, China. Issue 3 (June 2015) - Huang, Jinliang; Zou, Caineng; Dong, Dazhong; Li, Jianzhong; Wang, Yuman; Wang, Shejiao; Li, Denghua
The drilling data and test results of a large number of shale samples collected from Upper Triassic Xujiahe Formation, in the Sichuan Basin were used to find out the distribution characteristics, geochemical characteristics, reservoir characteristics and gas-bearing property of the continental shale in Xujiahe Formation, to figure out its resource prospects. The shale reservoir of the Xujiahe Formation was high in organic matter content (with a TOC content of 0.06% to 14.8%, 2.36% on average), with an organic matter of type III kerogen, Ro% of 0.8% to 3.0% (1.62% on average). In the high maturity stage of large quantity gas generation, it is rich in brittle mineral (>40%), and high in clay mineral content (average of 49.5%) which is mainly composed of mixed illite/smectite layer and illite. The shale is 1%–3% in porosity (2.73% on average). The pores are mainly nanoscale matrix ones (2 to 50 nm in size), and organic pores in local areas. The gas content of Xujiahe shale was measured at 3.01 m 3 /t, on average. This study suggests that Xujiahe shale has some gas resource potential; but, there are still a number of challenges and difficulties which need to be resolved in its exploration and development in the future.